The international sales accelerator: A project management tool for improving sales performance in foreign target markets - Alexander Gerybadze; Simone Wiesenauer (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
There is a current research gap in the marketing and management literature regarding the setup of sales and distribution structures as well as the rollout in foreign target markets in order to establish countrywide presences. Due to this gap, we developed the International Sales Accelerator Model. The data collection and verification of the model took place during a thirdparty funds project with Baden-Württemberg's business development agency, and environmental agency. The results reveal that the model represents a summary of best practices from different internationalization processes of very large companies. It is a seven-stage project management tool with the objective to improve the sales performance of companies entering foreign target markets.
urn:nbn:de:bsz:100-opus-14864
Keywords: 330; International Market Selection; Sales and Distribution Development in Foreign Markets; Environmental Technology Industry